Criterios que se aplican en la creación de contenidos visuales sobre las mujeres rurales en los medios digitales del Gobierno Autónomo Descentralizado Municipal Intercultural de Pujilí y la Organización de Pueblos Indígenas de Jatun Juigua - Escobar Suntasig, Jhoselyn Patricia (2023)
In the present project, the visual contents that are disseminated on social networks of the Pujilí Municipal Intercultural Decentralized Autonomous Government and the Organization of Indigenous Peoples of Jatun Juigua, with respect to rural women, were analyzed. For this reason, the processes that have occurred in the creation of their communication products were investigated, and in the same way the construction of said products was evidenced, which have been disseminated on their digital platforms. The objectives set out in this research were: to analyze the criteria applied in the creation of visual content about rural women in the digital media of the Intercultural Municipal Decentralized Autonomous Government of Pujilí and the Organization of Indigenous Peoples of Jatun Juigua.